RADIO DAN TAPE RECORDER SEBAGAI MEDIA PEMBELAJARAN - Muhammad Herfandi; Muhammad Wahyudi (Jurnal At-Tabayyun, 2023)
One of the learning media that can be used is radio and tape recorder. Radio is an auditory learning medium that can only be enjoyed through hearing aids. The effect of the actuality of radio can be served more quickly than television The problem discussed in this study is what is the essence of radio learning media and audio tape recorders? What is the history of radio and audio tape recorder In 1951, the public education service at the ministry of education and teaching, organized a radio broadcast program for public education. The target of radio education is mainly demobilized students, who after the end of the war of independence experienced many problems both returning to school and adjusting to society. Broadcasts are broadcast from self-service transmitters in Jakarta with an effective transmission radius of 10 km. Broadcast content is taken from high school study materials and actual materials from the communityhas some advantages and disadvantages. One of the advantages of radio that we can see clearly is that it is relatively cheap, but it has a drawback that often becomes an obstacle for teachers in using radio as a learning medium, which is very tied to broadcast schedules. While one of the advantages of Audio TapeRecorder is that it has a dual function, because it can present the results of the recording